Patrol reports - Australia. Department of Territories; Australian School of Pacific Administration (1949)
Extracts of patrol reports sent regularly to ASOPA. The extracts contain comments by patrol officers on customs and culture in Papua New Guinea and anthropological observations. Patrol officers include K.I. Chester, S.S. Smith, D.J. Clancy. F.P. Kaad, J.R. Stuntz, B.A. McCabe, R.S. Bell, A.J. Zweck, C.E. Terrell, W. Tomasetti, B.B. Butcher, C.G. Bowman, L. Doolan, J.K. McCarthy, G.R.G. Wearne, A.T. Carey, M. W. Brightwell, F.D. Anderson, S.H. Yeoman, T.W. White, J.D. Martin, W.R. Dishon. Also included is a list patrol reports sent to the Dept. of Territories.
Manuscript reference no. : NLA MS 7444.
The Australian School of Pacific Administration (ASOPA) is now called the Centre for Pacific Development and Training.
Keywords: Australia. -- Department of Territories -- Archives; Law enforcement -- Papua New Guinea; Peace officers -- Papua New Guinea; Papua New Guinea -- Social life and customs